Effect of Processing Speed on Microstructure and Colour Properties of the Iron Ore-Derived Red Colour Pigment - Woon H.S.; Ewe L.S.; Lim K.P.; Ismail I. (Institute of Physics Publishing, 2023)
Ball milling; Blending; Color; Economic geology; Iron ores; Mechanical alloying; Microstructure; Milling (machining); Sports; Colour properties; Colour value; Novel techniques; Pigment production; Processing speed; Rod milling; Pigments